ANALISA PENGARUH PENERAPAN METODE EDUCATION 3.0 PADA PEMBELAJARAN ENGLISH AS FOREIGN LANGUAGE MEMANFAATKAN MEDIA WHATSAPP DI PPNS - Wibowo Arninputranto; Lusia Eni Puspandari; Binti Mualifatul Rosydah (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2018)
Education and technology develops very rapidly and becomes a positive thing if both can be used together. Education 3.0 method is a teaching method where students can use technology to find references and discuss them with lecturers and other students. The WhatsApp application will be used as a learning media to study English as Foreign Language (EFL) along with the Education 3.0 method. This study aims to find out how important the use of WhatsApp media is and how far its function is based on students' perceptions. Data was obtained from a survey conducted on 90 respondent of EFL study participants. A pilot study was also conducted on 30 respondents to find out the reliability of the instrument in this study. A quantitative data were collected and accumulates total sample together with the percentages of returns. Data summary is used to identify the usefulness of the learning tool. The results of the study show that WhatsApp can significantly help students in learning EFL, but the activeness of students in participating in online lessons must also be considered so that WhatsApp can be truly effective in implementing the Education 3.0 method.